An Atypical Case of Shiga Toxin Producing-Escherichia Coli Hemolytic and Uremic Syndrome (STEC-HUS) in a Lung Transplant Recipient. (11th April 2019) - Manière, Louis; Domenger, Camille; Camara, Boubou; Giovannini, Diane; Malvezzi, Paolo; Rostaing, Lionel
Abstract : We herein describe the first case of thrombotic microangiopathy (TMA) which was related to Shiga toxin producing- Escherichia Coli Hemolytic and Uremic Syndrome (STEC-HUS) after lung transplantation. His maintenance immunosuppression relied on tacrolimus plus mycophenolic acid. TMA was treated with plasma exchanges (PE) (fresh frozen plasma substitution). After five days of PE, platelets count and lactate dehydrogenase level normalized, whereas hemoglobin continued to gradually decrease and no improvement in kidney function was observed. After seven PE sessions, all TMA biological signs resolved. However, kidney function did not improve, and the patient still required chronic dialysis.